2014
DOI: 10.1128/aem.00761-14
|View full text |Cite
|
Sign up to set email alerts
|

Murein Lytic Enzyme TgaA of Bifidobacterium bifidum MIMBb75 Modulates Dendritic Cell Maturation through Its Cysteine- and Histidine-Dependent Amidohydrolase/Peptidase (CHAP) Amidase Domain

Abstract: c Bifidobacteria are Gram-positive inhabitants of the human gastrointestinal tract that have evolved close interaction with their host and especially with the host's immune system. The molecular mechanisms underlying such interactions, however, are largely unidentified. In this study, we investigated the immunomodulatory potential of Bifidobacterium bifidum MIMBb75, a bacterium of human intestinal origin commercially used as a probiotic. Particularly, we focused our attention on TgaA, a protein expressed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 51 publications
0
22
0
2
Order By: Relevance
“…Among the bifidobacteria that colonize the human infant gut, members of the Bifidobacterium bifidum species deserve a special mention (Turroni et al ., ), as they have been shown to metabolize host‐derived glycans, in particular human milk oligosaccharides (HMOs) (Turroni et al ., ; Sela, ) and mucin (Turroni et al ., 2010; 2011a; Gonzalez‐Rodriguez et al ., ). Recent studies performed under in vitro conditions as well as using an in vivo murine model highlighted the occurrence of various extracellular proteins produced by members of the species B. bifidum , such as sortase‐dependent pili or the murein lytic enzyme TgaA, both of which are presumed to be pivotal for their interaction with their host (Turroni et al ., 2013; 2014a; Guglielmetti et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Among the bifidobacteria that colonize the human infant gut, members of the Bifidobacterium bifidum species deserve a special mention (Turroni et al ., ), as they have been shown to metabolize host‐derived glycans, in particular human milk oligosaccharides (HMOs) (Turroni et al ., ; Sela, ) and mucin (Turroni et al ., 2010; 2011a; Gonzalez‐Rodriguez et al ., ). Recent studies performed under in vitro conditions as well as using an in vivo murine model highlighted the occurrence of various extracellular proteins produced by members of the species B. bifidum , such as sortase‐dependent pili or the murein lytic enzyme TgaA, both of which are presumed to be pivotal for their interaction with their host (Turroni et al ., 2013; 2014a; Guglielmetti et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…One of the most studied mechanisms relates to the ability of probiotic bacteria to antagonize pathogenic organisms either by the excretion of antimicrobial agents (5) or by the displacement of pathogenic organisms through the competitive occupancy of adhesion sites (6). In addition, a number of reports suggest that health benefits result from stimulation of the immune system by components presented at the surfaces of probiotic strains (7,8). Both in vivo and in vitro experiments have demonstrated that the polysaccharides present at the surfaces of the bacteria, referred to either as capsule or as exopolysaccharides (EPSs), can play roles both in the displacement of pathogenic organisms and in the stimulation of the immune system (9,10).…”
mentioning
confidence: 99%
“…The strain was selected as a representative of a species that has been reported to possess numerous host interaction properties (9), including marked adhesion to enterocytes (10)(11)(12), immunomodulation (12)(13)(14), and metabolism of mucin and human milk oligosaccharides (15,16).…”
mentioning
confidence: 99%